(untitled) (AYUSHDHARA, 2018)
Ayurveda is one of the ancient sciences originated in India that describes the ways of healthy living. Mere absence of disease cannot be termed as health. To name so, there must not be any pathology too. It needs perfect sense of well-being. The classical texts of Ayurveda opine that vitiation of any of the Dosha Dhatu and Mala can cause ill health or disease, and hence they must be prevented or corrected at the earliest. Dyslipidemia is an easily preventable and controllable risk factor related to cardiovascular but, is an iceberg condition. It is not a disease in itself but a cause for or associated with many diseases. Ayurvedic classical texts have not directly described this condition in detail but there are few descriptions or names which can be related with dyslipidemia. This paper tries to conceptualize dyslipidemia as per Ayurveda based on Dosha, Dhatu and their Guna at the level of Mahabhuta. Here, an effort is made to term it as a condition given in texts but not as a disease.